Population Dynamics from Peripheral Regions: A North Atlantic Perspective - Godfrey Baldacchino (European Journal of Spatial Development)
This paper argues for the need to adopt a dynamic approach to demography and migration in the peripheral (often island or remote rural) regions of the North Atlantic. It cautions against the simplified and false dichotomy between gentrification and depopulation, calling rather for a more fluid appreciation of the manner in which people exploit opportunities for mobility as they connect with, and from, peripheral places. In so doing, the paper also identifies the limitations of both data-collection methodologies for demographic purposes, as well as public policy generally, wedded as these are to static categories of time and location. It also reviews qualitative material from Prince Edward Island, a small island province of Canada, which highlights why immigrants may privilege their mobility to ‘settling down’: some of the reasons given speak to the difficulty of ‘fitting into’ a tight, albeit friendly, island community. Finally, the paper suggests policies that may facilitate the better integration of geographically remote communities into the wider knowledge economy.